Sadia Shepard’s Foreign-Returned: Pakistani Immigrants’ View on American Values - Harendika, Melania Shinta; Ashila, Azka (Universitas Negeri Semarang, 2020)
Sadia Shepard’s Foreign-Returned talks about the life of Pakistani immigrants in America, especially Hasan, who struggle to live a better life in the U.S. American values become the main focus in this study to see their influences in certain characters’ point of view of this short story. The data are selected conversations and the narrations in Sadia Shepard’s Foreign-Returned as well as traditional American values and the sociological data of Pakistani Diaspora in America in the 2000s. This research reveals that most of the characters, both first- and second-generation Pakistani immigrants, practice American values in certain ways. However, values are fluid. Not everyone in the U.S.A believes in American values; on the other hand, non-Americans are possible to practice American values. In brief, how much the American values influence the characters' minds and behavior does not depend on whether they are first- or second-generation immigrants.